Educação no contexto do rompimento da Barragem de Fundão: representações sociais em movimento de educadores(as) sobre a escola no reassentamento de Bento Rodrigues - Adriane Cristina de Melo Hunzicker (2024)
The question proposed in this thesis was to investigate the process of re-territorialization of Bento Rodrigues Municipal School after the collapse of the Fundão Dam. The main aim of the work was to understand the educators' ways of thinking, feeling and acting about the school. As theoretical references, we used the approach of Social Representations in Movement in the field of Social Psychology; the triad of territorialization, deterritorialization and re-territorialization in the approach of Geography; and the concept of Pedagogical Silence under construction in the thematic field that studies the mining-disruption relationship and the reconstruction of ways of producing and reproducing existence. The methodological path took the following steps: a bibliographic review of theoretical references; observation research, data collection and seven narrative interviews during fieldwork; analysis of scientific, journalistic and documentary production to build up the school's trajectory; analysis of the narrative interviews with the interlocution of theoretical frameworks. The data from the narrative interviews showed that, faced with the challenges of the unfamiliar, the subjects interviewed were forced to make movements in their Social Representations based on the moments and spaces they experienced with the school. The representational movements were analyzed using four categories, whose narratives focused on: I) the experience of the school before the collapse, II) the processes of de-re-territorialization of the school experienced in Mariana, III) the disconnection from previous experiences, emphasizing the school in Novo Bento Rodrigues, IV) the school in Novo Bento Rodrigues, but which move through the times/spaces of the school. The educators intensified their representational movements to anchor and objectivize each of these categories. Among the results of their ways of thinking, feeling and acting about the school, it was observed feelings that ranged from sadness, joy, fear, indignation, idealization, and especially, uncertainty about various factors, such as the continued operation of School in the future and guaranteed access to school transport for students and teachers who will not be living in the resettlement were observed. Practices of struggle for the guarantee of rights were observed, for example, efforts to access the rebuilt school to promote school events before the final handover. These efforts aimed to build belonging and identity ties with the space, as well as the realization of pedagogical projects about the past, present and future of Bento Rodrigues. On the other hand, the professionals did not take part in decision-making about the construction of the school and limitations in accessing information about the unfamiliar object were observed, situations that reverberate in the absence of knowledge and, consequently, in Pedagogical Silence in educational practice on the subject of the rebuilt school.